Contractual Commitments, Bargaining Power, and Governance Inseparability: Incorporating History into Transaction Cost Theory - Argyres, Nicholas S.; Liebeskind, Julia Porter (Academy of Management Review, 1999)
Nicholas S. Argyres, Julia Porter Liebeskind, Contractual Commitments, Bargaining Power, and Governance Inseparability: Incorporating History into Transaction Cost Theory, The Academy of Management Review, Vol. 24, No. 1 (Jan., 1999), pp. 49-63